Designing with bamboo across cultures: Reflections on material-led pedagogy in the ITB–UiTM collaborative design workshop - Raditya Ardianto Taepoer; Slamet Riyadi; Abu Hanifa Ab. Hamid; Muhammad Ridhwan; Dinah Rakhim; Muhammad Ihsan (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
Material-led approaches have become increasingly relevant in design education because they support embodied learning, cultural sensitivity, and collaborative practice. This paper reflects on a three-day bamboo design workshop conducted collaboratively by Institut Teknologi Bandung (ITB), Indonesia, and Universiti Teknologi MARA (UiTM) Cawangan Kedah, Malaysia. Rather than evaluating the workshop only through final student products, the study examines how learning emerged through material exploration, cultural interpretation, and collaborative making. Adopting a practice-based design research approach, the study analyzes sketches, concept boards, material experiments, prototypes, photographs, presentation materials, and final artifacts produced by eight mixed student groups. The cross-group analysis identifies three main findings. First, bamboo acted as an active material mediator that shaped decisions related to form, construction, scale, and feasibility. Second, shared Indonesia–Malaysia cultural references, including festive rituals, weaving traditions, and everyday material culture, were translated into contemporary product concepts through abstraction rather than literal representation. Third, the short workshop duration encouraged students to adopt minimum viable product strategies, prioritizing workable functions, iterative refinement, and collective decision-making. The paper contributes to material-led design education by showing how short-term cross-cultural workshops can be understood as pedagogical settings where artifacts serve as evidence of material negotiation, cultural translation, and collaborative learning.Published Date: 2026-07-22